Dari Konsep Satu Jenis Patogen S. mutans ke Interaksi Mikrobioma - Perubahan Paradigma untuk Metode Pencegahan ECC yang Lebih Efektif - Gunawan, Paulina N.; Bachtiar, Endang W.; Rizal, Mochamad F. (e-GiGi, 2025)
Abstract: Early childhood caries (ECC) remains a progressive and multifactorial oral health problem in children. For decades, Streptococcus mutans has been regarded as the primary pathogen due to its acidogenicity, aciduricity, and strong biofilm-forming ability. However, emerging evidence indicates that ECC is a polymicrobial disease influenced by complex interactions within the oral microbial community. Dental biofilm functions as a dynamic ecosystem where microorganisms interact, exchange metabolites, and adapt to environmental changes. Disruption of this ecological balance can shift the biofilm from a healthy to a dysbiotic and cariogenic state. Other species such as S. wiggsiae, utilizing the fructose-6-phosphate shunt pathway and S. sputigena, which forms “superstructure” biofilms with S. mutans have been shown to enhance ECC severity. Conversely, protective bacteria including Rothia spp., C. matruchotii, S. sanguinis, and S. oralis help maintain plaque pH and biofilm balance. Understanding the dynamic interplay between pathogenic and protective bacteria underscores the need for microbiome-based preventive strategies, such as probiotics, nitrate supplementation, and personalized risk assessment. This approach may provide a more effective and sustainable prevention method compared with conventional strategies. In conclusion, by understanding ECC as a polymicrobial disease that is influenced by the dynamic of pathogenic and protective bacteria, prevention strategies based on microbioma can be chosen as a more effective solution than the conventional strategies focusing solely on the elimination of S. mutans. Keywords: early childhood caries; oral microbiome; protective bacteria; biofilm. Abstrak: Early childhood caries (ECC) merupakan masalah kesehatan gigi anak yang progresif dan multifaktorial. Selama beberapa dekade, Streptococcus mutans dianggap sebagai patogen utama karena sifat asidogenik, asidurik, dan kemampuannya membentuk biofilm. Bukti terkini menunjukkan bahwa ECC merupakan penyakit polimikroba yang dipengaruhi oleh interaksi kompleks komunitas oral. Biofilm gigi berperan penting sebagai ekosistem dinamis tempat bakteri berinteraksi, bertukar metabolit, dan beradaptasi terhadap perubahan lingkungan. Ketidakseimbangan dalam komunitas biofilm dapat menggeser kondisi dari sehat menjadi disbiotik dan kariogenik. Spesies lain seperti S. wiggsiae dengan jalur fructose-6-phosphate shunt, S. sputigena yang membentuk “superstructure” biofilm bersama S. mutans, terbukti meningkatkan keparahan ECC. Sebaliknya, bakteri protektif seperti Rothia spp., C. matruchotii, S. sanguinis, dan S. oralis berperan menjaga pH plak dan keseimbangan biofilm. Pemahaman terhadap dinamika antara bakteri patogen dan protektif ini menekankan perlunya strategi pencegahan berbasis mikrobioma, seperti probiotik, suplementasi nitrat, dan analisis risiko personal. Simpulan studi ini ialah dengan memahami ECC sebagai penyakit polimikroba yang dipengaruhi oleh dinamika bakteri patogen dan protektif maka dapat dilakukan pencegahan yang berbasis mikrobioma yang lebih efektif dibandingkan strategi konvensional yang hanya berfokus pada eliminasi S. mutans. Kata kunci: early childhood caries; mikrobioma oral; Streptococcus mutans; bakteri protektif; biofilm